Determination of Contraction-Induced Changes in Elbow Flexor Cross-Sectional Area for Evaluating Muscle Size-Strength Relationship During Contraction. Issue 6 (June 2015) - Akagi, Ryota; Iwanuma, Soichiro; Hashizume, Satoru; Kanehisa, Hiroaki; Fukunaga, Tetsuo; Kawakami, Yasuo
Abstract : Abstract: Akagi, R, Iwanuma, S, Hashizume, S, Kanehisa, H, Fukunaga, T, and Kawakami, Y. Determination of contraction-induced changes in elbow flexor cross-sectional area for evaluating muscle size-strength relationship during contraction. J Strength Cond Res 29(6): 1741–1747, 2015—The aims of this study were to determine contraction-induced changes in the elbow flexor cross-sectional area (CSA) and to examine whether the maximal CSA during a high-intensity contraction is more closely related to the strength than that at rest in the elbow flexors. Fourteen young male subjects participated in this study. The elbow flexor CSAs were measured at sites from 1 cm proximal to 6 cm distal to the reference site (60% of the upper arm length from the acromial process of the scapula to the lateral epicondyle of the humerus) (every 1 cm; 8 sampling sites) using magnetic resonance imaging, at rest and during 10, 20, 40, 60, and 80% of maximal voluntary contraction (MVC) of isometric elbow flexion. The elbow flexor CSA changed greatly during low-intensity contractions, and this contraction-induced change was small over 60%MVC. Compared with at rest, greater CSA around the muscle belly and smaller CSA in the distal portion of the elbow flexors were found in contracted conditions. The MVC strength was significantly correlated with the maximal CSAs at rest and each contraction level, but stepwise multiple regression analysis selected only that during 80%MVC as a significant contributor for estimating the MVC strength. These results suggest that, in the elbow flexors, the contraction-induced change in the CSA reaches its peak under high contractile level and that the maximal CSA during 80%MVC is more closely related to the MVC strength than that at rest.